Torsional contact between elastically similar flat-ended cylinders - Kartal, M; Hills, D; Nowell, D; Barber, J (Elsevier, 2010)
The problem of frictional contact between two long, elastic, coaxial cylinders pressed together, end-to-end and subsequently subjected to monotonically increasing or oscillating torque is considered and the full state of stress found, together with the partial slip regime and the strength of the assembly.